PELATIHAN DASAR-DASAR MANAJEMEN DAN BUSINESS MODEL CANVAS BAGI PETANI TEMBAKAU DI KABUPATEN CIANJUR - Rejito Cattleya; Fachrilla Virsahaya; Dewi Adifa Putri (COMVICE: Journal Of Community Service, 2023)
The capacity-building activities for human resources in the tobacco agriculture sector in Kabupaten Cianjur through basic management training and the Business Model Canvas (BMC) aim to enhance the management capabilities of the tobacco farming business. This activity aims to highlight the importance of adaptation and innovation in tobacco agribusiness management to improve competitiveness and sustainability. This training provides managerial knowledge and skills to tobacco farmers and related stakeholders. Through a training methodology involving discussions, simulations, and case studies, participants are trained to understand and apply management principles and to plan effective business models using BMC. The results of the training activities indicate an increase in participants' capacity and understanding of agribusiness management, as well as the development of cooperation and communication networks among participants. This activity is expected to improve the productivity and sustainability of the tobacco agriculture sector in Kabupaten Cianjur.